Probing the molecular and structural elements of ligands binding to the active site versus an allosteric pocket of the human farnesyl pyrophosphate synthase. Issue 5 (1st March 2015) - Gritzalis, Dimitrios; Park, Jaeok; Chiu, Wei; Cho, Hyungjun; Lin, Yih-Shyan; De Schutter, Joris W.; Lacbay, Cyrus M.; Zielinski, Michal; Berghuis, Albert M.; Tsantrizos, Youla S.
Graphical abstract: Bisphosphonate chameleons that suggest a feed-back regulatory role for an allosteric pocket of the human farnesyl pyrophosphate synthase. Abstract: In order to explore the interactions of bisphosphonate ligands with the active site and an allosteric pocket of the human farnesyl pyrophosphate synthase (hFPPS), substituted indole and azabenzimidazole bisphosphonates were designed as chameleon ligands. NMR and crystallographic studies revealed that these compounds can occupy both sub-pockets of the active site cavity, as well as the allosteric pocket of hFPPS in the presence of the enzyme's Mg 2+ ion cofactor. These results are consistent with the previously proposed hypothesis that the allosteric pocket of hFPPS, located near the active site, plays a feed-back regulatory role for this enzyme.